Molecular genetic and epigenetic mechanisms of primary and secondary resistance to imatinib mesylate treatment in ph chromosome positive chronic myeloid leukemia patients - Elias, Marjanu Hikmah (2015)
Imatinib mesylate (IM) is a BCR-ABL targeted tyrosine kinase inhibitor drug used for frontline therapy in patients with chronic myeloid leukemia (CML). IM is highly effective and is considered the standard of care in CML management. Even though IM has become the gold standard frontline treatment of CML, resistance to IM has emerged as a major problem of concern. Nearly 33% of CML patients on IM therapy develop resistance which can be either due to BCR-ABL dependent or BCR-ABL independent mechanisms. BCR-ABL dependent mechanism involves point mutation in the BCR-ABL tyrosine kinase domain and amplification of the BCR-ABL gene. BCRABL independent mechanisms include several factors including alteration in pharmacokinetics of IM with respect to absorption, distribution of metabolism as well as epigenetic alterations. The present study was undertaken to elucidate the BCR-ABL dependent mechanism and BCR–ABL independent mechanism involving epigenetic alterations, in Malaysian CML patients undergoing IM therapy. A total of 205 CML patients on IM therapy (122 IM resistant and 83 IM good response) were included in this study. Using denaturing High Performance Liquid Chromatography (dHPLC) followed by DNA sequencing, 122 IM resistant CML patients were screened for BCR-ABL mutations. Ninety two IM resistant CML patients who did not show BCR-ABL mutations (BCR-ABL non-mutated) were investigated for BCR-ABL gene amplification. As part of epigenetic approach, 175 CML patients comprising of 83 good response and 92 IM resistant BCR-ABL non-mutated CML patients were subjected to Methylation Specific High Resolution Melt Analysis (MS-HRM). In BCR-ABL mutation analysis, mutations were detected in 30/122 patients (24.6%) with two of the CML patients showing double mutations. Seventeen different types of mutations (T315I, G250E, E255K, E255V, M351T, Y253H, V289F, E355G, F359V, L387M, H396R, E355A, D276G, A397P and E281K) including two novel mutations (G251E and N368S) were identified. Since different mutations confer different levels of resistance, detection as well as characterization of BCR-ABL mutations is highly relevant in CML patients to guide in selecting the most suitable IM dosage or changing to other Tyrosine kinase inhibitor therapy. However, the 92 IM resistant BCR-ABL non-mutated CML patients did not show amplification of the BCR-ABL gene. With regard to BCR-ABL independent mechanism, methylation levels of HOXA4 and HOXA5, but not of SOCS1, were found to be higher in CML patients showing resistance. IM treated CML patients with higher than 62.5% of HOXA4 and HOXA5 promoter methylation levels were found to be associated with a higher risk (OR, 4.71; 95% CI, 2.46, 9.03; P<0.001 and OR, 4.26; 95% CI, 2.22, 8.17; P<0.001, respectively) for developing IM resistance compared to the optimal response group. Promoter hypermethylation of HOXA4 and HOXA5 genes could be considered as one of the BCR-ABL independent mechanisms mediating IM resistance and could be a potential epigenetic biomarker in supplement to the BCR-ABL gene mutation in predicting IM treatment response among CML patients. In a five-year survival analysis, the presence of BCR-ABL mutations especially Y253H and E355G mutations (p-value =0.005 and p-value =0.025 respectively), were found to be associated with the prognosis and survival of CML patients on IM therapy. However, after adjusting for other variables in multiple Cox regression analysis, CML stage has emerged as the only significant prognostic factor (HR: 27.04, p-value <0.001 for BP and HR: 9.58, p-value <0.001 for AP). The overall results suggest that resistance to IM is not due to a single or simple mechanism, but is a multi-factorial phenomenon. BCR-ABL mutations could be considered as molecular marker for predicting the IM response as well as prognosis of CML patients on IM treatment whereas promoter methylation levels of HOXA4 and HOXA5 could be considered as epigenetic markers for predicting the response to IM.